Development of the information society in Poland on the example of households - Mariusz Pyra; Tomasz Gustyn (Rozprawy Społeczne)
Abstract The development of the information society in Poland, as a key component of socio-economic progress, is evidenced by a range of indicators, one of which is the use of information and communication technologies in households.